Have data leaks been plugged?. Issue 3 (27th May 2020) - Baxter, Michael
Abstract : A new analysis suggests that UK government statistics were once leaking early, but no longer. Michael Baxter reports Abstract : A new analysis suggests that UK government statistics were once leaking early, but no longer. Michael Baxter reports.